1988
DOI: 10.1002/ajim.4700130606
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective cohort mortality study of workers exposed to formaldehyde in the garment industry

Abstract: In order to assess the possible human carcinogenicity of formaldehyde we conducted a retrospective cohort mortality study of workers exposed for at least three months to formaldehyde in three garment facilities which produced permanent press garments. A total of 11,030 workers contributing 188,025 person-years were included in the study. Vital status was successfully ascertained through 1982 for over 96% of the cohort. The average (TWA) formaldehyde exposure at the three plants monitored in 1981 and 1984 by NI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 13 publications
2
42
0
Order By: Relevance
“…The plants studied by Won g (36) and Fayerweather et al (40) also included some workers that were studied by Blair et al (25). Two plants were included in both studies by Sta yner (33,34). In the summation of the observed and expected numbers, howe ver, results from the earlier study by Sta yner (33) and the studies by Marsh (35), Fayerweath er et al (40), Wong (36), and Liebling et al (37) were not included because they were generally covered in the lat er study by Stayner et al (34) or in the study by Blair et al (25) .…”
Section: Summary Of Epidemiologic Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The plants studied by Won g (36) and Fayerweather et al (40) also included some workers that were studied by Blair et al (25). Two plants were included in both studies by Sta yner (33,34). In the summation of the observed and expected numbers, howe ver, results from the earlier study by Sta yner (33) and the studies by Marsh (35), Fayerweath er et al (40), Wong (36), and Liebling et al (37) were not included because they were generally covered in the lat er study by Stayner et al (34) or in the study by Blair et al (25) .…”
Section: Summary Of Epidemiologic Resultsmentioning
confidence: 99%
“…Other casereferent studies in the United States (60) and Nordic countries (61) found no association between formaldehyde exposure and nasal cancer, but they were not specifically designed to assess risks from this chemical. Several cohort studies of industrial workers or professional workers have also failed to detect excesses of nasal cancer (23,25,34) although the power of the studies was small.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations